Liberalization and Universal Access to Basic Services : Telecommunications, Water and Sanitation, Financial Services, and Electricity - Organisation for Economic Co-operation and Development (OECD and the World Bank, Paris, 2013)
Access to basic services plays an important role in both individual well-being and a country's economic development. For this reason, general availability of these services to citizens, regardless of income level and geographical location, has generally been viewed as an important public policy goal. However, the precise definition of this goal and the means of attaining it have provoked controversy. This volume explores whether liberalization can contribute to achieving universal service goals and, if so, how, and looks at the types of complementary policies that may be required. It focuses on experience in four sectors: telecommunications, financial, water and sanitation, and energy services. For each sector, an overview paper and one or two case studies from developing countries examine the experience of governments in harnessing liberalization to meet social goals. It is hoped that this cross-sector view will yield general insights which a focus on a single sector may not, and help each sector to generate ideas by drawing upon experience in other sectors. A horizontal assessment also helps to determine how far the services negotiations at the World Trade Organization (WTO), under the general agreement on trade in services can aid or impede the attainment of universal service goals.